DECISIONS RELATED TO HIGHER EDUCATION IN THE NATIONAL EDUCATION COUNCILS - Ozkayacan, Melek; Neyişci , Nilay (International Online Journal of Education and Teaching, 2025)
National Education Councils are the most important educational meetings in our country, which give direction to the National Education System and the education system in Turkey with the agenda items and decisions taken regarding the education system and educational policies. Due to the importance of these meetings, it has been tried to examine how and in which subject contents the decisions taken in the National Education Councils regarding higher education were handled. All written policies, documents and strategies of the twenty National Education Councils held between 1939-2021 were taken as the main source in order to determine the importance given to higher education in the National Education Councils, which are the highest advisory body of our education system, to evaluate the extent to which higher education education was included in which councils and to determine the decisions taken regarding higher education. In the study, since primary sources related to all content were accessed and it was deemed appropriate to include all Council meetings in the study, written (printed and digital) documents related to the National Education Councils were scanned and examined without selecting any sample in the data search, and the data were evaluated by descriptive analysis and content analysis. Keywords: National Education Councils, Higher Education, Council Decisions, Education